Training of Teachers through Face-To-Face Contact Mode Vs. Online - Tulsi, P. K.; Poonia, M. P.; Bala, Anku (Journal of Engineering Education Transformations, 2015)
The institute started offering in-service training programmes for technical teachers through the use of information&communication technologies (ICT)in the year 2012. Initially, Induction Training Programmes were started. The feedback from the participants was quite encouraging and the institute could train almost double the number of teachers during 2012-13. Thus, from the year 2013-14, content matter updating programmes through the use of videoconferencing were also started. During 2013Â¬14, programmes in the area of Electronics and Communication Engineering were organized both through face-to-face contact mode and online (video conferencing) in which 199 and 319 teachers working in technical institutions participated respectively. Participants' reactions were studied with respect to the various aspects of the programmes namely course contents, competence of faculty, training strategy, outcomes, and utility at workplace. Though a slight decline was observed in the ratings of various aspects of the programmes offered through online but no major differences were observed. A large number of technical teachers could be trained through online inÂ¬service training programmes in comparison to programmes organized through regular contact mode.